2017
DOI: 10.1111/1467-9817.12117
|View full text |Cite
|
Sign up to set email alerts
|

Developmental aspects of reading motivation and reading achievement among second grade low achievers and typical readers

Abstract: This investigation examined developmental aspects of 155 second-graders' intrinsic reading motivation and reading achievement at the beginning and end of a school year. Reading motivation remained at the same level through the school year, while reading achievement was significantly higher at the end of it than at the beginning. According to word reading skills, low reading achievers (n = 63) and typical readers (n = 92) evinced significant differences in reading motivation. The former scored lower in overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
52
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 55 publications
8
52
0
4
Order By: Relevance
“…For example in the EFL context, teachers can incite students' confidence to read when the difficulty level is lower or matches students' comprehension level but can also cause the opposite when the difficulty level is higher instead. In reality, it is found that students who do not read are: learners who do not find the material to be interesting, those who believe its importance do not apply to them, and low achievers whose confidence declines overtime (Miyamoto, Pfost & Artlet, 2018;Vaknin-Nusbaum et al, 2018). By selecting their own materials, it enhances the relatability of the reading content to the students' background and ability, thus contributing to their motivation.…”
Section: Motivation In Readingmentioning
confidence: 99%
“…For example in the EFL context, teachers can incite students' confidence to read when the difficulty level is lower or matches students' comprehension level but can also cause the opposite when the difficulty level is higher instead. In reality, it is found that students who do not read are: learners who do not find the material to be interesting, those who believe its importance do not apply to them, and low achievers whose confidence declines overtime (Miyamoto, Pfost & Artlet, 2018;Vaknin-Nusbaum et al, 2018). By selecting their own materials, it enhances the relatability of the reading content to the students' background and ability, thus contributing to their motivation.…”
Section: Motivation In Readingmentioning
confidence: 99%
“…When students read because they earnestly enjoy reading, they are intrinsically motivated to read (Pintrich & Schunk, 2002;Schiefele et al, 2012). Intrinsic reading motivation has a significant positive impact on reading achievement (Gottfried, Fleming, & Gottfried, 2001;Becker, M., McElvany, N., & Kortenbruck, M., 2010;Vaknin-Nusbaum, Nevo, Brande, & Gambrel, 2017). Beginning in elementary school, differences between students who are intrinsically motivated to read and those who are not are already apparent (Vaknin-Nusbaum et al, 2017).…”
Section: Motivation and Reading Motivationmentioning
confidence: 99%
“…Intrinsic reading motivation has a significant positive impact on reading achievement (Gottfried, Fleming, & Gottfried, 2001;Becker, M., McElvany, N., & Kortenbruck, M., 2010;Vaknin-Nusbaum, Nevo, Brande, & Gambrel, 2017). Beginning in elementary school, differences between students who are intrinsically motivated to read and those who are not are already apparent (Vaknin-Nusbaum et al, 2017). As early as second grade, students who struggle with reading exhibit a decrease in intrinsic reading motivation while strong readers' intrinsic reading motivation remains stable (Vaknin-Nusbaum et al, 2017).…”
Section: Motivation and Reading Motivationmentioning
confidence: 99%
See 2 more Smart Citations